Quality of Life at Patients with Malignancies (The Eurasia Proceedings of Educational and Social Sciences, 2019)
The subject of this research is the quality of life at patients with Myeloma Multiplex at diagnosis and during therapy within 6 to 12 months. The research aims to analyze patients to be able to continue activities which will contribute for improving their quality of life as a priority task for patient, his family, health institutions and social environment. This research was conducted at the University Clinic for Hematology, period from 2009 to 2012. It covers patients with multiple myeloma. Total of 80 patients, using the EORTC QLQ C30 ver. 3.0 standardized questionnaires for quality of life that analyzed the physical, cognitive, emotional, personal and social functions related to the patients. It also analyzed and general health and quality of life. Physical functioning at diagnosis is 27.5 during treatment 59.5, significantly improved. Personal functioning at patients at the diagnosis is 17.9, during therapy -36.4. Emotional functioning at patients at diagnosis is 39.9, during the therapy over 73.3. Cognitive functioning was at diagnosis 55.2, during treatment 72.5. Social functioning was 26.2 at the diagnosis; during the treatment 50.8. Financial difficulties were at diagnosis’s 76.2 and 72.5 during treatment. Overall health and quality of life has a value of 23.9, and during therapy 58.8.Quality of life at patients with myeloma multiplex was significantly improved as a result of on time diagnosis and treatment with modern medicaments and the role of social worker with the application of certain social skills, continuous counseling, guidance and education for their reintegration in the community.
Keywords: Quality of life; Patient; Health